1995
DOI: 10.1164/ajrccm.152.3.7663790
|View full text |Cite
|
Sign up to set email alerts
|

Peak expiratory flow monitoring is not a reliable method for establishing the diagnosis of occupational asthma.

Abstract: This is a study of the reliability of peak expiratory flow (PEF) monitoring using a portable computerized peak flow meter, the VMX Mini-log, in 17 subjects referred for suspected occupational asthma. Subjects were requested to monitor their PEF six times daily using the VMX Mini-Log for 2 wk at work and at least 10 d away from work. They were unaware that their readings were stored by the flow meter in addition to the digital readout. Four subjects (22%) were unable to complete the monitoring. The results reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 10 publications
2
30
0
3
Order By: Relevance
“…In a study of 17 subjects instructed in the use of a portable computerized peak flow meter who were unaware that their readings were being stored by the flow meter, it was found that only 55% of the records were completely accurate in terms of the recorded value and timing of the measurements (48 the presence of airflow limitation and its reversibility; in the absence of airflow limitation, the presence of nonspecific airway hyperresponsiveness; and the demonstration of work-relatedness of asthma by objective means (38). The Canadian Thoracic Society has suggested a similar approach in making the diagnosis ofoccupational asthma, by demonstrating the presence of asthma with pulmonary function tests and then assessing the relationship between asthma and work (40).…”
Section: Clinical Picturementioning
confidence: 99%
“…In a study of 17 subjects instructed in the use of a portable computerized peak flow meter who were unaware that their readings were being stored by the flow meter, it was found that only 55% of the records were completely accurate in terms of the recorded value and timing of the measurements (48 the presence of airflow limitation and its reversibility; in the absence of airflow limitation, the presence of nonspecific airway hyperresponsiveness; and the demonstration of work-relatedness of asthma by objective means (38). The Canadian Thoracic Society has suggested a similar approach in making the diagnosis ofoccupational asthma, by demonstrating the presence of asthma with pulmonary function tests and then assessing the relationship between asthma and work (40).…”
Section: Clinical Picturementioning
confidence: 99%
“…36 Another study found similar results, with only 55.3% of the measured records being completely accurate as to PEF level and time. 37 In the present study, we eliminated workers whose peak flow readings were influenced by an outlier and workers who did not complete at least five days of the testing. Peak flow is effort-dependent, meaning that the harder the person blows into the meter, the greater his or her measured PEFR will be.…”
Section: Discussionmentioning
confidence: 99%
“…Dado que la prueba es esfuerzo-dependiente es necesaria una adecuada supervisión. Para evitar la manipulación de los datos se pueden utilizar dispositivos de medición de PEF o FEV1 electrónicos que almacenan la información registrada 27 . La mejor forma de interpretar los registros es el análisis global por un clínico experimentado.…”
Section: Diagnóstico Funcionalunclassified